Sungkai Leaves (Peronema Canescens) Ameliorates the Plasma Glucose Profile and the Pancreatic Histopathological Regeneration of Diabetic Wistar Rats - Def Primal; Risya Ahriyasna; Rahmita Yanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to test how effective oral infusion of sungkai leaves is on the profile of changes in blood plasma glucose levels and regeneration of pancreatic tissue in diabetic Wistar rats. This research method is a proper experimental design with a randomized pre-post-test design with a control group. The study's results illustrate differences in mice's blood sugar levels before and after the intervention, showing a decrease in blood sugar levels in the K(+), P-1, and P-2 groups, while in the K(+), P-1, and P groups -2. The K(-) group shows a decreasing trend. Apart from that, histopathological examination of the pancreas also showed improvement in each treatment group with a decreasing percentage of pathological events. In conclusion, blood plasma glucose examination showed a significant difference, positively affecting diabetes mellitus, while the rate of pancreatic tissue injury showed a similar form. Keywords: Sungkai leaves, plasma glucose, pancreatic regeneration